'Capture the Most Subtle Conflicts of the Soul' in the Transaltion Process. The Poetry of Wisława Szymborska in Galician and in Spanish - Jackiewicz, Aleksandra (Madrygal. Revista de Estudios Gallegos, 2019)
The purpose of this article is to point out the possible translation obstacles encountered by translators when recreating the world depicted in the poetry of Wisława Szymborska, winner of the 1996 Nobel Prize for Literature. We propose to carry out a comparative study between the original verses and the Galician and Spanish versions to find out if the stylistic and formal structure of the works from which emerges “a very peculiar emotional and intellectual vibration, due to a mixture of very concrete observations and a sober lyrical tone, always attenuated by the irony” (Rodowska 2008) has been preserved in the target texts. Our study will be based on the idea of the translation of lyrical texts as a reworking of the original in another language (Herrero Cecilia 1995) and on the theory of “lateral thinking” (De Bono 1970), that is, a mode of imaginative and anarchic reasoning, which dictates the functional organization of the brain that determines the habits of thinking. The analysis carried out following these conceptions will allow us to verify to what extent the stimulation in the translators of the development of their recreational potential to pour the Polish verses has enabled the receiver to perceive the qualities of the original reality. Likewise, we will demonstrate that the aesthetic intentionality of the Szymborska’s representations can be a part of the Galician and Spanish poetic context without major inconveniences.
Keywords: Poetry; Translation; Lateral Thinking; Recreation; Wisława Szymborska